GENERASI Z BERINVESTASI SYARIAH : IKUTI PELATIHAN, TINGKATKAN PENGETAHUAN - Rinwantin Rinwantin (Politeknik Bisnis Indonesia, 2022)
Knowing the factors that influence Gen Z's interest in investing in sharia is important to answer Gen Z's concerns about financial problems in the future. The increase in Sharia shares is an opportunity for varied and promising investment choices in the future, especially supported by the characteristics of Gen Z who are easy to learn new things and are familiar with the internet and the applications offered. This study aims to find out what factors influence Gen Z's interest in sharia investing. Obtained as many as 95 samples online. The data was processed using SPSS 26 with the results of Adjusted R2 of 0.412 and the results of the t test which concluded that the results of H1 and H3 were accepted, and H2 was rejected. The training variable has a sig value of 0.000 <0.05 and a coefficient of 0.067 the Knowledge variable has a sig value of 0.039 <0.05 and a coefficient of 0.136. So it can be concluded that in order to increase the interest of Gen Z, it is necessary to conduct training and increase knowledge about sharia investment, so that Gen Z who will be the next generation of the nation can feel financial freedom.